Germany : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
Fiscal policy has a strong foundation in the multiyear program of spending cuts, tax reforms, and deficit reduction in Germany. Germany's focus on actual, rather than cyclically adjusted, fiscal goals and outcomes carries the risk of rendering fiscal policy procyclical. The recent business and personal income tax reforms, pension reform, and product market reforms is commendable. But the potential benefits of these diverse reforms require a more proactive approach to labor market reform. The longer-term efficiency and functioning of the financial sector pose challenging issues.